A study of expressed emotion, perceived stress and socio-demographic profile in patients of dissociative disorder - Singh, Nitesh Kumar; Gupta, Pankaj; Yadav, Jai Singh (International Journal of Research in Medical Sciences, 2020)
Background: Dissociation is understood as one of coping mechanism to deal with intense stressors. Individuals vary widely in their subjective response to a similar stressful event depending on number of factors including their family and social support system. So, authors tried to study the expressed emotion in patients of dissociative disorder along with other socio-demographic factors and its relation with perceived stress. Methods: This cross-sectional descriptive study was done on 100 patients with primary diagnosis of dissociative disorder. Hamilton depression rating scale (HAM-D) was used to assess comorbid Depressive symptoms and Hamilton anxiety rating scale (HAM-A) was used to asses comorbid anxiety symptoms. Perceived stress scale (PSS) was used to assess the perception of stress. Family emotional involvement and criticism scale (FEICS) was used to measure perceived criticism (PC) and intensity of emotional involvement (EI). Results: Mean perceived stress in this study was 25.8. Mean score for perceived criticism (PC) was 16.5 and emotional involvement (EI) was 15.7. Both measures of expressed emotions were significantly higher in females and subjects belonging to joint families and rural area. In this study perceived stress by subjects was significantly (p=0.001) correlated to perceived criticism (Pearson r = 0.78) and emotional involvement (Pearson r = 0.77). Conclusions: High perceived criticism and emotion over involvement of family member was associated with perceived stress in dissociation patients.